Analisis Pengendalian Kualitas dengan Menggunakan First Pass Yield dan Fishbone Diagram Pada PT X - Sri Susilawati Islam; Fatkhurozak Fatkhurozak (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2018)
Industrial competition in the current global industrial era is not only influenced by product prices but also influenced by customer satisfaction with the products, one of the factors that influence customer satisfaction is the quality of the products, for which quality control is needed. This studies aims to measure the level of quality control as seen from the percentage of defective products and customer satisfaction. This research was conducted at PT X which is a cable producing company. The method used in this studies is the First Pass Yield to measure the percentage of defective products, Customer Complaints and production claims related to the quality of raw materials & haspels to measure customer satisfaction through questionnaires. From data processing, the average value of First Pass Yield is 94.2% which indicates the average rate of defective products per month is 5.8%. Customer complaints show customers are not satisfied with the Non Standard Length relating to the marker and cable length. So as to improve product competitiveness we provide several improvement proposals based on the fault categoriesthat arise.